Practical Research Methods : A User-Friendly Guide to Mastering - Catherine Dawson (UBS Publishers', 2002)
Define your project -- Decide upon a methodology -- Research methods -- Background research -- Participants -- Prepare a research proposal -- Conduct interviews -- Focus groups -- Contructing questionnaires -- participant observation -- Analyse your data -- Report your findings -- Be an ethical researcher.